Aging modulated by the Drosophila insulin receptor through distinct structure-defined mechanisms. Issue 2 (5th January 2021) - Yamamoto, Rochele; Palmer, Michael; Koski, Helen; Curtis-Joseph, Noelle; Tatar, Marc
Abstract: Mutations of the Drosophila melanogaster insulin/IGF signaling system slow aging, while also affecting growth and reproduction. To understand this pleiotropy, we produced an allelic series of single codon substitutions in the Drosophila insulin receptor, InR . We generated InR substitutions using homologous recombination and related each to emerging models of receptor tyrosine kinase structure and function. Three mutations when combined as trans-heterozygotes extended lifespan while retarding growth and fecundity. These genotypes reduced insulin-stimulated Akt phosphorylation, suggesting they impede kinase catalytic domain function. Among these genotypes, longevity was negatively correlated with egg production, consistent with life-history trade-off theory. In contrast, one mutation ( InR 353 ) was located in the kinase insert domain, a poorly characterized element found in all receptor tyrosine kinases. Remarkably, wild-type heterozygotes with InR 353 robustly extended lifespan without affecting growth or reproduction and retained capacity to fully phosphorylate Akt. The Drosophila insulin receptor kinase insert domain contains a previously unrecognized SH2 binding motif. We propose the kinase insert domain interacts with SH2-associated adapter proteins to affect aging through mechanisms that retain insulin sensitivity and are independent of reproduction.